Radical pancreatic cancer surgery: with arterial resection - Klaiber, Ulla; Mihaljevic, André Leopold; Hackert, Thilo (Translational gastroenterology and hepatology, 2019)
Extended surgery with arterial resection in pancreatic cancer remains a controversial topic. Although not recommended as a standard procedure, arterial resection may be feasible in selected patients and with the availability of new multimodal treatment approaches it may gain increasing impact in pancreatic cancer therapy as a complete tumor removal is still the only opportunity to achieve long-term survival for this disease. With regard to the surgical approach, one must differentiate between resection and reconstruction of the celiac axis and the hepatic artery as its most important branch, and resection/reconstruction of the superior mesenteric artery. Both procedures are technically possible and require a distinct level of surgical experience as well as interdisciplinary management for preoperative diagnosis and treatment of postoperative complications to achieve good outcomes. Besides arterial resection followed by reconstruction, there are specific situations when arteries may be resected without reconstruction, e.g., during distal pancreatectomy with celiac axis resection. In addition, in some cases arterial resections can be avoided despite a suspected tumor attachment by sharp dissection on the adventitial layer of the respective artery, especially after neoadjuvant therapy which is increasingly performed for borderline resectable and locally advanced tumor findings. This review summarizes definitions, diagnostics, technical aspects and outcomes of arterial resection in pancreatic cancer surgery in the context of the current literature and evidence.
Gesehen am 24.07.2020